2016
DOI: 10.3389/fpsyg.2016.00424
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the “Fit” between the Patient and the Therapy: The Role of Patient Gender in Selecting Psychological Therapy for Distressing Voices

Abstract: The experience of hearing distressing voices has recently attracted much attention in the literature on psychological therapies. A new “wave” of therapies is considering voice hearing experiences within a relational framework. However, such therapies may have limited impact if they do not precisely target key psychological variables within the voice hearing experience and/or ensure there is a “fit” between the profile of the hearer and the therapy (the so-called “What works for whom” debate). Gender is one asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…In this study, we tested whether gender differences in voice hearing experiences can be explained by differences in relating to voices. Our results replicated previous findings that female voice hearers tend to have more severe voice hearing experiences (Murphy et al 2010), report more negative emotions and distress due to voice hearing (Toh et al 2020), and tend to relate less functionally (Hayward et al 2016) when compared to male voice hearers. In general, significant effect sizes were small to medium (0.37 ≤|d|≤ 0.59).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, we tested whether gender differences in voice hearing experiences can be explained by differences in relating to voices. Our results replicated previous findings that female voice hearers tend to have more severe voice hearing experiences (Murphy et al 2010), report more negative emotions and distress due to voice hearing (Toh et al 2020), and tend to relate less functionally (Hayward et al 2016) when compared to male voice hearers. In general, significant effect sizes were small to medium (0.37 ≤|d|≤ 0.59).…”
Section: Discussionsupporting
confidence: 89%
“…When comparing male and female patients with a schizophrenia diagnosis and auditory hallucinations, gender differences were predominantly found in the emotional impact of voice hearing, with female participants reporting more negative feelings of shame, guilt, and anxiety due to voices (Toh et al 2020). Finally, Hayward et al (2016) found that female voice hearers prefer more distance when relating to their voices and reported more avoidant behavior and negative emotions due to their voices. In sum, previous research already points to gender differences in voice distress and voice relating, which suggests a possible connection between these variables.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Though gender and perceptions of masculinity/ femininity are known factors influencing various aspects of social interaction including power differentials and social appraisals (Eagly 1987;Maccoby, 1990;Rudman and Glick 2008;Ridgeway 2008), little is known about respective gender differences in the voice hearing experience. The only study explicitly investigating gender differences in voice appraisals and interrelating with voices in a quantitative design found more powerful emotional reactions to voices as well as a tendency to respond to them in a more resistant manner in women (Hayward et al 2016b). Furthermore, the study found that women appraised their voices as being more omnipotent, malevolent, and dominant compared to men (Hayward et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The only study explicitly investigating gender differences in voice appraisals and interrelating with voices in a quantitative design found more powerful emotional reactions to voices as well as a tendency to respond to them in a more resistant manner in women (Hayward et al 2016b). Furthermore, the study found that women appraised their voices as being more omnipotent, malevolent, and dominant compared to men (Hayward et al 2016b). However, the study had a number of methodical limitations, and although gendered relating styles are not stable but depend strongly on the gender category membership of each interaction partner (Jacklin and Maccoby 1978), they did not account for differences due to variations in the interactional constellations, e.g., male voice hearer on male voice vs. male voice hearer on female voice, etc.…”
Section: Introductionmentioning
confidence: 99%